Expression of Tailored α-N-Acetylglucosaminidase in Escherichia coli for Synthesizing Mannose-6-Phosphate on N-Linked Oligosaccharides of Lysosomal Enzymes - Yunsong Cao; Wei Wang (Bioengineering)
Lysosomal enzymes are synthesized as N-glycosylated glycoproteins with mannose-6-phosphate (M6P) moieties, which are responsible for their binding to M6P receptors and transporting to the lysosome. In the M6P biosynthetic pathway, a Man8GlcNAc2 glycoform is converted to M6P groups through two consecutive enzymatic reactions, including N-acetylglucosamine (GlcNAc)-1-phosphotransferase (GNPT), transferring GlcNAc-1-phosphate from UDP-GlcNAc to the C6 hydroxyl groups of mannose residues, and then, removal of the covering GlcNAc moiety from the GlcNAc-P-mannose phosphodiester was carried out using an α-N-acetylglucosaminidase (referred to as ‘uncovering enzyme’, UCE) in the trans-Golgi network (TGN). Here, we expressed differently tailored versions of the UCE, including four truncated variants, in Escherichia coli. The four variants with the signal peptide, transmembrane domain, propiece and cytoplasmic tail truncated, respectively, were purified by affinity chromatography, and their enzymatic activities were assayed using a UDP-Glo kit. By fusing a maltose-binding protein (MBP) in the N-terminus of the UCE variants, the fusion proteins could be soluble when expressed in E. coli. The highest concentration of the purified enzyme was 80.5 mg/L of fermentation broth. Furthermore, the UCE with the core catalytic domain exhibited the highest uncovering activity.